(3QMdI jhSa YKeGf GdegfOS eY GdNOjhi ESeGYjd Edi aQfSG SfI (B1867s
(3ChdgG (B:s
(3hcGf GdbjGe ef ScfOQjg s
(3BNQgG (B:s
(3ajGdgG ef ahGjO YXjeI eajOI dCYeGd hWfkG ai GdhbJ faSg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3LZQGajG (B944) s
Keywords: (3GdLZQGajG h GdHdOGfs